Integrating AI-powered tools and technopreneurship for enhancing educational communication and innovation - Chee, Wei Yeoh; Zi, Jian Oh (Universiti Teknologi MARA, Kedah, 2024)
The rapid digitalization in education necessitates innovative tools to enhance communication and foster entrepreneurship. Educational institutions struggle to maintain effective communication and foster innovation due to outdated methods and a lack of integration between technology and entrepreneurship. This project aims to integrate AI-powered tools and technopreneurship principles to enhance communication in educational settings and promote innovative thinking. Conducted through a series of webinars involving 672 participants from 33 institutions, the project covered AI-enhanced meetings, live chat innovations, and technopreneurship strategies. Findings showed significant improvements in communication efficiency, engagement, and administrative tasks, as well as encouragement of innovative solutions among participants. The project demonstrated that combining AI tools with technopreneurship principles can transform educational communication and foster a culture of innovation, providing a comprehensive solution to modern educational challenges.